Microemulsion dispersion of sulfuric acid in a hydrocarbon medium - B. V. Pokidko; V. A. Lukin; V. V. Bulavtsev (Тонкие химические технологии, 2014)
The present paper discusses the results of experiments on the preparation of sulfuric acid inverse emulsions in the media of different liquid alkanes. Attention was put on the influence of system composition on the performance emulsions stabilized by a cationic surfactant – dialkyldimethylammonium chloride and a series of aliphatic alcohols (hexanol, ethylhexyl alcohol etc) used as co-surfactants. The phase diagram was obtained, and the optimal composition was found. Besides, estimation of particle size distribution in the systems was provided by dynamic light scattering technique.